Interferon-γ enhances the therapeutic effect of mesenchymal stem cells on experimental renal fibrosis - Ryo Kanai (Nature Portfolio, 2021)
Abstract Mesenchymal stem cells (MSCs) administered for therapeutic purposes can be activated by interferon-γ (IFN-γ) secreted from natural killer cells in injured tissues and exert anti-inflammatory effects. These processes require a substantial period of time, leading to a delayed onset of MSCs’ therapeutic effects. In this study, we investigated whether pretreatment with IFN-γ could potentiate the anti-fibrotic ability of MSCs in rats with ischemia–reperfusion injury (IRI) and unilateral ureter obstruction. Administration of MSCs treated with IFN-γ strongly reduced infiltration of inflammatory cells and ameliorated interstitial fibrosis compared with control MSCs without IFN-γ treatment. In addition, conditioned medium obtained from IFN-γ-treated MSCs decreased fibrotic changes in cultured cells induced by transforming growth factor-β1 more efficiently than that from control MSCs. Most notably, secretion of prostaglandin E2 from MSCs was significantly increased by treatment with IFN-γ. Increased prostaglandin E2 in conditioned medium obtained from IFN-γ-treated MSCs induced polarization of immunosuppressive CD163 and CD206-positive macrophages. In addition, knockdown of prostaglandin E synthase weakened the anti-fibrotic effects of MSCs treated with IFN-γ in IRI rats, suggesting the involvement of prostaglandin E2 in the beneficial effects of IFN-γ. Administration of MSCs treated with IFN-γ might represent a promising therapy to prevent the progression of renal fibrosis.